The Relationship of Clean and Healthy Living Behavior and the Incidence of Malaria: Systematic Review - Rusni; Winarti, Eko; Agung Mirasa, Yudied; Soares, Ivo Da Costa (Jurnal Ilmiah Kesehatan, 2024)
Malaria is a tropical disease caused by the bite of the Anopheles mosquito. Malaria is an infectious disease that is of global concern. This disease still often causes extraordinary events. This disease can attack all individuals regardless of age and gender. Factors related to the incidence of malaria are the environment and community behavior. Clean and Healthy Living Behavior is a set of behaviors practiced based on awareness because of learning in the health sector, and it plays an active role in realizing public health. One effort to eradicate malaria is clean and healthy living behavior. This research analyzes the relationship between Healthy, Clean-Living Behavior and malaria incidence. Systematic Review (PRISMA) is used. All articles that pass the selection are then reviewed and summarized based on the purpose, author name, year published, instruments used, research results, and suggestions for further research. The results of this literature research aim to implement healthy and clean-living habits to avoid environments that cause malaria. It is also more optimal to build a clean environment by implementing clean and healthy living behaviors, which will ultimately have a good effect on health. Malaria is one of the infectious diseases that is still a public health problem in the world, including Indonesia.